Contágios poéticos no espaço: por ações no contexto urbano - Maroso, Elias Edmundo (2014)
This master s dissertation refers to a research in Visual Poetics/Art and Technology whose interest lies in the creation of urban interventions and their artistic derivations through actions and objects projected by analog and digital resources, which intend to establish relations of contagion with the context of insertion. As accounts in a possible arrangement, the text is characterised by the distribution of artistic propositions in accordance with topics covered in three chapters. Such an approach begins with a discussion of elements that are fundamental and leading of actions in the city, where contagion is circumscribed in the quality of operating concept linked to site-specific procedures. The process of realisation of the artistic procedures follows premises of the cartographic method and of the principles of poietic as from a trajectory that pervades philosophical remarks on the diagram, the encounter, and the combination. Subsequently, considerations are developed regarding the urban milieu and the practices that take the everyday as their field of action, connected to the actions produced during this research. Besides routines of observation on the street, of emphatic link with the photographic register, the object as a tridimensional category in visual arts is explored and highlights a way of constructing through projections on digital graphic softwares so that they are, in some cases, materialised and installed in architectural monuments in the urbe. As a result of the research, eight propositions in art are presented, which comprehend the usage of different technical resources, being these anchored on frameworks and references that take as their problems the ethical-aesthetic usage of language, the crossing of several places, and the art implied in the social-political sphere.